2016
DOI: 10.1590/0103-6440201600701
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Desensitization in Teeth Affected by Amelogenesis Imperfecta

Abstract: The aim of this paper was to describe a clinical case of immediate dental desensitization using a self-etch adhesive system in an adolescent patient diagnosed with amelogenesis imperfecta (AI). AI was associated with severe tooth sensitivity, treated by the application of a universal adhesive system for desensitization of the teeth affected by AI. Reduction of tooth sensitivity was assessed using a visual analog scale during all reevaluations. The technique was effective for reducing tooth sensitivity. It was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
0
5
0
3
Order By: Relevance
“…Studies on fluorosis have been largely limited to the permanent dentition, with reported global prevalence ranging between 6.7% and 32.2% [23] and few studies indicating association between caries and fluorosis in the permanent dentition [24,25]. Caries is also associated with amelogenesis imperfecta in the permanent dentition [26]. There is a scarcity of studies about the association between fluorosis, amelogenesis imperfecta and ECC in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on fluorosis have been largely limited to the permanent dentition, with reported global prevalence ranging between 6.7% and 32.2% [23] and few studies indicating association between caries and fluorosis in the permanent dentition [24,25]. Caries is also associated with amelogenesis imperfecta in the permanent dentition [26]. There is a scarcity of studies about the association between fluorosis, amelogenesis imperfecta and ECC in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…A higiene bucal geralmente apresenta-se insatisfatória devido à sensibilidade apresentada, tornando o paciente mais susceptível ao manchamento por café, cigarro e alimentos. Além das deficiências quantitativas e qualitativas, algumas anomalias podem estar associadas como taurodontismo e má-formação radicular, calcificação pulpar, reabsorção radicular e coronária, falha na erupção e impactação de dentes permanentes ou agenesia, crescimento gengival e doença periodontal, além de problemas oclusais como mordida aberta anterior e posterior (Azevedo, et al, 2013;Moreira, et al, 2016). Quandalle, et al (2020), afirmam que alguns relatos de casos documentaram controle deficiente de placa, acúmulo de cálculo dentário e inflamação gengival entre os pacientes com AI, porém, há poucas informações sobre a sensibilidade e o estado periodontal de pacientes portadores da AI; e que se faz necessário mais estudos acerca das condições periodontais associadas aos diferentes subtipos de AI.…”
Section: Principais Condições Clínicas Evidenciadasunclassified
“…26 In addition, a self-etch system seemed particularly indicated because of the patient's sensitivities. 27,28 Selective enamel etching was performed in accordance with current recommendations. [29][30][31] A two-step self-etch adhesive could have been preferred to optimize the adhesion durability, 32,33 but it is better to use a cement with its corresponding bonding agent.…”
Section: Bonding To Ai-affected Teethmentioning
confidence: 99%